2014
DOI: 10.3390/ijerph110707154
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes and Antibiotic Resistances of Campylobacter jejuni Isolates from Cattle and Pigeons in Dairy Farms

Abstract: Campylobacter jejuni is the most common food-borne zoonotic pathogen causing human gastroenteritis worldwide and has assumed more importance in Italy following the increased consumption of raw milk. Our objectives were to get an overview of genotypes and antibiotic resistances in C. jejuni isolated from milk, cattle feces, and pigeons in dairy herds of Northern Italy. flaB-typing was applied to 78 C. jejuni isolates, previously characterized by Multi-Locus Sequence Typing, and genotypic resistances towards mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This CC is frequently associated with cases of human disease and is one of the most frequently reported CCs in poultry (Dingle et al., 2001 ; Kärenlampi et al., 2007 ; Kittl et al, 2013b ; Manfreda et al., 2016 ; EFSA and ECDC, 2021 ); however, CC‐21 has also been found in cattle (Pezzotti et al., 2003 ; EFSA and ECDC, 2021 ), sheep (Lucarelli et al., 2016 ), turkey (Lo Schiavo et al., 1991 ) and the environment (Dingle et al., 2001 ). Several studies were performed in Italy and show how common this CC is not only in chickens but also in strains isolated from turkeys, cattle and bulk tank milk (Lo Schiavo et al., 1991 ; Bianchini et al., 2014a , b ). The most common CC among chicken C. jejuni isolates was the CC‐21 according to that documented worldwide (Pezzotti et al., 2003b ; EFSA and ECDA, 2014 ; Lucarelli et al., 2016 ; Cito et al., 2018 ; Sarhangi et al., 2021 ).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…This CC is frequently associated with cases of human disease and is one of the most frequently reported CCs in poultry (Dingle et al., 2001 ; Kärenlampi et al., 2007 ; Kittl et al, 2013b ; Manfreda et al., 2016 ; EFSA and ECDC, 2021 ); however, CC‐21 has also been found in cattle (Pezzotti et al., 2003 ; EFSA and ECDC, 2021 ), sheep (Lucarelli et al., 2016 ), turkey (Lo Schiavo et al., 1991 ) and the environment (Dingle et al., 2001 ). Several studies were performed in Italy and show how common this CC is not only in chickens but also in strains isolated from turkeys, cattle and bulk tank milk (Lo Schiavo et al., 1991 ; Bianchini et al., 2014a , b ). The most common CC among chicken C. jejuni isolates was the CC‐21 according to that documented worldwide (Pezzotti et al., 2003b ; EFSA and ECDA, 2014 ; Lucarelli et al., 2016 ; Cito et al., 2018 ; Sarhangi et al., 2021 ).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…In a recent survey conducted in Northern Italy, C. jejuni was detected in 12% of the bulk tank milk samples that were examined ( Bianchini et al, 2014 ), and some disease outbreaks have been reported in the same Italian regions (two in Emilia Romagna, one in Veneto, and one in Marche) following the consumption of raw milk from self-service automatic vending machines ( Amato et al, 2007 ; Arrigoni et al, 2009 ; Petruzzelli et al, 2011 ). Despite no official data existing for the incidence of campylobacteriosis associated with raw milk consumption, quantitative risk assessment modeling has estimated that the worst possible scenario for human infections with C. jejuni linked to the consumption of raw milk in Italy would exceed 300,000 cases per year ( Giacometti et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that prevalent STs of C. jejuni and C. coli isolated from cattle in Japan were ST806 and ST21, and ST1068 (Asakura et al 2012;Asakura et al 2019;Sasaki et al 2020). ST21 of C. jejuni and ST1068 of C. coli are also prevalent in cattle in Italy, USA., and the UK, demonstrated that the host associations of Campylobacter genotypes are more robust than their geographic variations (Kwan et al 2008;Sanad et al 2011;Roux et al 2013;Bianchini et al 2014;Jonas et al 2015;Cha et al 2017;Sheppard et al 2010). The top three STs of C. jejuni and the most frequent ST (ST1068) of C. coli would be adaptable to beef cattle and widely spread to beef farms in Japan.…”
Section: Open Accessmentioning
confidence: 99%